(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new classes of multifunctions called upper almost nearly (τ_1,τ_2)-continuous multifunctions and lower almost nearly (τ_1,τ_2)-continuous multifunctions. Moreover, several characterizations and some properties concerning upper almost nearly (τ_1,τ_2)-continuous multifunctions and lower almost nearly (τ_1,τ_2)-continuous multifunctions are established.